(untitled) (Journal of Bio-Science, 2023)
Petroleum ether (PE), chloroform (CHCl3), and methanol (CH3OH) extracts of the whole chickpea plant Cicer arietinum (L.) have been tested against adult beetles of Callosobruchus chinensis (L.), Sitophilus oryzae (L.) and Tribolium castaneum (Herbst) through dose-mortality and repellent activity tests. In dose mortality tests, the PE extracts of C. arietinum gave LD50 values of 3.466, 3.292, 2.721, 2.398, 1.887, 1.663 and 1.428 mg/cm2 against C. chinensis and 4.297, 3.415, 2.246, 1.725, 1.384, 0.984 and 0.722 mg/cm2 against S. oryzae both after 12, 18, 24, 30, 36, 42 and 48 h of exposures, respectively. The CHCl3 extracts gave LD50 values of 5.242, 4.844, 3.472, 2.945, 2.540, 1.875, 1.295 and 1.053 mg/cm2 against C. chinensis after 6, 12, 18, 24, 30, 36, 42 and 48 h of exposures, respectively. The CH3OH extracts, on the other hand, yielded LD50 values of 0.923, 0.757, 0.649, 0.515, 0.400, 0.303, 0.247 and 0.197 mg/cm2 against C. chinensis, 4.227, 3.528, 3.454, 2.933, 2.493, 2.187, 1.938 and 1.724 mg/cm2 against S. oryzae and 3.485, 3.176, 2.851, 1.531, 1.113, 0.756, 0.534 and 0.478 mg/cm2 against T. castaneum adults after 6, 12, 18, 24, 30, 36, 42 and 48 h of exposures, respectively. However, the PE extracts of C. arietinum did not show any mortality against T. castaneum and the CHCl3 extracts were inactive against S. oryzae and T. castaneum adults. In repellency tests, all three organic extracts did not show any repellency against the test beetles. According to their intensity of activities, the extracts could be arranged in the following descending order: CH3OH extracts against C. chinensis > CH3OH extracts against T. castaneum > PE extracts against S. oryzae > CHCl3 extracts against C. chinensis > PE extracts against C. chinensis > CH3OH extracts against S. oryzae adults. The present results indicate that the test plant C. arietinum contains bioactive compounds and could be used as a source of control agents for the stored product pests. J Bio-Sci. 30(1): 91-100, 2022 (June)